Enugu State of Nigeria: approved budget estimates for 1993 - Government of Enugu State, Nigeria (Enugu: Government of EnuguState of Nigeria, 1993)
This volume provides details of the 1994 approved budget estimates for Government of Enugu State of Nigeria.
aia 14/02/2019
Loans
Keywords: Budget; Expenditure, public; Nigeria